CYP303A1 has a conserved function in adult eclosion in Locusta migratoria and Drosophila melanogaster. (October 2019) - Wu, Lixian; Jia, Qiangqiang; Zhang, Xubo; Zhang, Xueyao; Liu, Suning; Park, Yoonseong; Feyereisen, René; Zhu, Kun Yan; Ma, Enbo; Zhang, Jianzhen; Li, Sheng
Abstract: Insect cytochrome P450 monooxygenases (CYPs) play essential roles in both xenobiotic metabolism and developmental processes. However, the exact physiological function of many CYP genes remains largely unknown. Screening the expression of the CYP genes from the CYP2 and mitochondrial CYP clans of Drosophila melanogaster revealed that Cyp303a1 is highly expressed in the pupal stage. Knockdown of CYP303A1 transcripts by RNAi using the Gal4/UAS system with a ubiquitous driver ( tubulin-Gal4 ) in Drosophila or by dsRNA injection in the last nymph stage of Locusta migratoria resulted in severe defects in eclosion and lethality during and after adult emergence. In Drosophila, tissue-specific RNAi of Cyp303a1 with a wing-specific driver ( MS1096-Gal4 ) revealed that Cyp303a1 was essential for wing extension. Stage-specific RNAi of Cyp303a1 using Gal80 ts for thermal-dependent-suppression found that the expression of Cyp303a1 at the middle pupal stage was absolutely required. Meanwhile, Cyp303a1 mutants exhibited more than 80% lethality at the late embryonic development stages. Embryonic lethality of the Cyp303a1 mutants was fully rescued by the ubiquitous overexpression of exogenous Cyp303a1 . Taken together, we conclude that Cyp303a1 is indispensable for embryonic development and adult eclosion in D. melanogaster, the latter role being conserved over 400 million years of insect evolution. Graphical abstract: Image 1 Highlights: Cyp303a1 is highly expressed in the pupal stage with the highest level in the wings at 48h APF. Knockdown of CYP303A1 in Drosophila and Locusta resulted in lethality during and after adult emergence. Cyp303a1 mutants are arrested in the late embryonic stage, which can be rescued by the ubiquitous expression of Cyp303a1.